Concise enantioselective synthesis of 1-[(S)-3-(dimethylamino)-3,4 dihydro-6,7-dimethoxyquinolin-1(2H)-yl]propan-1-one, (S)-903 - Jagdale, Arun R.; Reddy, R. Santhosh; Sudalai, Arurnugam (Tetrahedron-Asymmetry, 2009)
A concise enantioselective synthesis of (S)-903, an inotropic agent, is described in nine linear steps and 95% ee based on asymmetric dihydroxylation of cinnamate ester and Co-catalyzed Multifunctional reduction of several functional groups leading to the construction of core tetrahydroquinolin-3-ol, as the key steps. (C) 2009 Elsevier Ltd. All rights reserved.